Spores that crush the spine in infancy: a diagnostic dilemma for an infant with special tuberculosis - Mohamed, Mossad Abdelhak Shaban; Mossad, Manar
We are presenting a seven months old girl with spastic paraplegia. The case highlights the dilemma with the diagnosis we encountered until establish the final diagnosis which is spinal tuberculosis. We highlighted a lot of important lessons.